Home bias at the fund level - Hau, Harald 1966-; Rey, Hélène (Working paper series / National Bureau of Economic Research, 2008)
"This paper presents new stylized facts on the distribution of the home bias at the fund level. We find (i) a large heterogeneity in the degree of home bias across mutual funds; (ii) a positive correlation between the size of funds and home bias; and (iii) a positive correlation between the size of funds, the number of foreign countries and the number of sectors in which they invest. These facts constitute a challenge for existing theories"--National Bureau of Economic Research web site